Identification of Subgenus C Adenoviruses by Fiber-Based Multiplex PCR - Adhikary, Arun Kumar (American Society for Microbiology, 2004)
Subgenus C human adenoviruses, which include serotypes 1, 2, 5, and 6, are often associated with respiratory illness, ocular infections, gastroenteritis, and systemic infection among immunocompromised patients. To address the problems associated with the conventional typing methods, we developed a fiber-based multiplex PCR assay for simple and specific identification of adenovirus type 1, 2, 5, and 6 field isolates. To design type-specific primers, adenovirus type 1 and 6 fiber genes were sequenced. The assay correctly identified prototype strains of adenovirus serotypes 1, 2, 5, 6, as well as 21 previously typed adenovirus field isolates. Mixing two different prototype DNAs produced two amplicons of different lengths, thus clearly distinguishing the prototypes. The results correlated 100% with serological tests and 95% with the previously described PCR-restriction fragment length polymorphism method. The detection of dual infection is an added benefit of the assay. No nonspecific amplification was detected with other adenovirus serotypes or with nonadenoviral DNA. Our fiber-based multiplex PCR assay will provide a convenient tool for type-specific identification of subgenus C adenovirus isolates in various clinical situations and in epidemiological investigations and is a better alternative than the hexon-based assay.